IMPROVING STUDENTS’ WRITING ACHIEVEMENT BY USING SANDWICH PARAGRAPH STRATEGY - Fitri Novia; Eva Saptarina (Universitas Islam Ogan Komering Ilir Kayuagung, 2019)
Writing is important skill that should be taught. However, many students reluctant to do writing activities. Sandwich Paragraph Strategy is one of strategies that can be used to overcome students’ problems in writing. The purpose of this study was to find out whether or not there was a significant difference in writing achievement between the students who were taught through Sandwich Paragraph strategy and that of those who were not.Quasi-experimental method was used in this study.The participants of this study were the eighth grade students of SMPN 2 Teluk Gelam. Purposive sampling techinuqe was used to select the sample. T-test was used to calculate the data. Based on the result, it was found that t-obtained (4.002) was higher than t-table (2.003). It meant that there was a significant difference in writing achievement between the students who were taught through Sandwich Paragraph Strategy and that of those who were not. Thus, Sandwich Paragraph Strategy could improve students’ writing achievement